Indonesian Novice English Teachers’ Identity Formation: Getting Along with Tensions - Cendra, Anastasia Nelladia (IJET (Indonesian Journal of English Teaching), 2019)
In the early years of teaching, beginning teachers should make a lot of adjustments while dealing with many expectations from others, which may cause some tensions for them. Under a narrative inquiry framework, the researcher collected reflective stories of five Indonesian beginning teachers of English language and interviewed them to examine common tensions experienced and how they cope with these tensions. The findings revealed 19 kinds of tensions they were facing, ranging from the more common tensions to contextual tensions. Furthermore, four common coping strategies were identified, namely looking for solutions by themselves (negotiating, choosing one stream, and learning more about something), accepting as the situation as it is, receiving help without asking, and sharing with significant others. It is suggested that fellow teachers, school staff, and related authorities give more to help beginning teachers handle the tensions. Keywords: beginning teachers, coping strategies, identity, tensions